Aristolochia bhamoensis is a taxonomic synonym of A. tongbiguanensis, and now the correct name is Isotrema tongbiguanense - Zhu, Xin-Xin; Liao, Shuai; Tan, Yun-Hong; Shen, Jian-Yong; Ma, Jin-Shuang (Phytotaxa, 2019)
Aristolochia tongbiguanensis and A. bhamoensis are considered to be the same species based on the examination of related protologues, type specimens and living plant photos. Therefore, the latter is treated here as a synonym of the former, which is congruous with Zhu et al. (2019) and now the correct name is Isotrema tongbiguanense.